Strategi Pemasaran Keripik Singkong Pada Ud. Daffa Keripik Di Desa Lau Dendang Kabupaten Deli Serdang: indonesia - Selly Sabrina Nasution; Tina Herianty Masitah; Faisal Azhari Baldan Panjaitan (Universitas Khairun, 2026)
This study aims to evaluate the marketing approach used by UD. Daffa Keripik in Lau Dendang Village, Deli Serdang Regency and to formulate appropriate business development steps based on a SWOT analysis. The method used in this study is field research with a qualitative descriptive approach. Data were collected through observation, interviews, documentation, and distribution of questionnaires to selected informants using the snowball sampling technique. Data analysis was carried out using the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, and SWOT analysis. The findings of the study indicate that the IFE value is 2.8 and the EFE value is 2.9, which places the business in Quadrant I. This position indicates that UD. Daffa Keripik has internal strengths that can be utilized to maximize external opportunities. Therefore, the recommended strategy is the SO (Strengths-Opportunities) strategy that focuses on business development. This strategy includes product development based on consumer needs, continuous product quality improvement, brand strengthening, design innovation and packaging variations, and improving product quality control. The implementation of this strategy is expected to increase competitiveness, expand market share, enhance customer loyalty, and encourage sustainable business growth. Keywords: marketing, SWOT analysis, IFE, EFE, cassava chips, MSMEs